2019
DOI: 10.1111/nph.15906
|View full text |Cite
|
Sign up to set email alerts
|

Growing season moisture drives interannual variation in woody productivity of a temperate deciduous forest

Abstract: Summary The climate sensitivity of forest ecosystem woody productivity (ANPPstem) influences carbon cycle responses to climate change. For the first time, we combined long‐term annual growth and forest census data of a diverse temperate broadleaf deciduous forest, seeking to resolve whether ANPPstem is primarily moisture‐ or energy‐limited and whether climate sensitivity has changed in recent decades characterised by more mesic conditions and elevated CO2. We analysed tree‐ring chronologies across 109 yr of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 84 publications
(137 reference statements)
2
41
0
Order By: Relevance
“…These findings support Maxwell et al (2016), where they found trees in in this region to have a weakening signal to soil moisture, termed the "Fading Drought Signal." The recent decrease in sensitivity of tree growth to soil moisture has also been documented outside of the ORV, in the Mid-Atlantic US (Helcoski et al,2019), indicating the impact of a changing climate could influence the representation of tree rings to climate in mid-latitude locations. Drought in the Midwest during the instrumental period was temporally clustered in the 1930s and 1950s.…”
Section: Orv and Lbda Validation Statisticsmentioning
confidence: 87%
See 2 more Smart Citations
“…These findings support Maxwell et al (2016), where they found trees in in this region to have a weakening signal to soil moisture, termed the "Fading Drought Signal." The recent decrease in sensitivity of tree growth to soil moisture has also been documented outside of the ORV, in the Mid-Atlantic US (Helcoski et al,2019), indicating the impact of a changing climate could influence the representation of tree rings to climate in mid-latitude locations. Drought in the Midwest during the instrumental period was temporally clustered in the 1930s and 1950s.…”
Section: Orv and Lbda Validation Statisticsmentioning
confidence: 87%
“…In both cases, the northern portions of the region experienced severe drought (in excess of -4.0 PMDI values for 1988), but the southern portion of the region only experienced moderate dryness (PMDI values of ~ -2.0). Maxwell et al (2016) attributed the weakening signal to a recent period without severe drought; however, Helcoski et al (2019) discussed the possibility of increases in carbon dioxide concentrations in addition to a long period of wetness interacting to weaken tree growth responses to soil moisture. However, recent works examining the simultaneous influence of water availability, carbon dioxide concentrations, and acidic deposition found that water availability was the leading influence on tree growth (Levesque et al, 2017;Maxwell et al, 2019), suggesting a wet period is likely driving the weakening signal.…”
Section: Orv and Lbda Validation Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a handheld 4.3 mm diameter increment borer to extract two samples from each tree at breast height from opposite sides of the tree (Stokes and Smiley, 1968) All newly collected samples were mounted and sanded with progressively finer sandpaper to reveal ring structure. We used the list method to visually cross-date all samples (Yamaguchi, 1991), and then the program COFECHA (Holmes, 1983) to statistically verify the cross-dating. For the three updated chronologies, we cross-dated the new sampled series with those previously sampled and available through the ITRDB.…”
Section: Ohio River Valley Tree-ring Networkmentioning
confidence: 99%
“…The narrow habitat requirements for this species could render mature trees susceptible to future changes in climate conditions. Previous studies have demonstrated that tulip polar was sensitive to variation in climate conditions (Martin-Benito and , Maxwell and Harley 2017, Helcoski et al 2019.…”
Section: Introductionmentioning
confidence: 98%